The Effect of Providing Classical Music Therapy on Anxiety Levels in Menopausal Women in the Munjul Jaya Health Center Area, Purwakarta, Indonesia - Mariska, Ika (Arkus, 2023)
Menopause is a time in a woman's life when menstruation or menstruation stops. Menopause occurs naturally after the age of 45 years. During menopause, a woman will experience various kinds of changes within herself. The changes that arise, both physically and psychologically, such as anxiety, can disrupt a woman's daily life, and this can cause anxiety for women facing menopause. One way to reduce anxiety is to use classical music therapy distraction techniques. This study aims to determine the effect of classical music therapy on anxiety levels in menopausal women in the Pisangan Region, East Ciputat, South Tangerang. The research method uses a pre-experiment method with one pre-and post-test design group. The sampling technique used was purposive sampling with 22 respondents. The Hamilton Anxiety Rating Scale (HARS) is used to assess anxiety. The research data were analyzed using statistical tests, namely the Wilcoxon test. The results of this study show an effect of classical music therapy on the anxiety level of menopausal women with a value of (p=0.000).